Work-life balance practices and organizational cynicism: The mediating role of person-job fit - Kakar, Abdul Samad; Kruger, Niel; Durrani, Dilawar Khan; Khan, Muhammad Asif; Meyer, Natanya (Frontiers in Psychology, 2022)
This study aims to elaborate on how Work-Life Balance (WLB) practices influence organisational cynicism (OC) through the mediation effects of person-job fit. We collected data from 331 nurses through a self-administered survey, and we tested our hypothesized model through partial least square structural equation modelling techniques using SmartPLS software. The findings revealed that WLB practices influenced OC negatively and PJF positively. We further found that PJF negatively influenced OC and mediated WLB practices' effect on OC. These findings imply that nurses should be provided WLB practices to meet their job and home responsibilities and thus have a less cynical attitude towards the organisation.